Kecemasan dan merokok dengan kejadian andropause - Dwi Hariyanti; Miftahudin Husni (Health Sciences and Pharmacy Journal, 2019)
Andropause prevalence can be estimated based on population projections. Andropause is a syndrome of decreasing in physical ability, sexual, and psychological. Some studies have shown that smoking can cause disruption of sexual function which is a symptom of andropause. The period of andropause in men's lives has a psychological impact that needs to be understood. To determine the correlation of anxiety and smoking with the incidence of men andropause in Wonoboyo. Type of the research was an analytic observation research with cross sectional approach. The place was in Wonoboyo on May 2018. The population was 96 men in Wonoboyo, 67 respondents were using simple random sampling. Correlation analysis used bivariate Spearman's rho and supported by cross tabulation. The value of anxiety correlation with andropause was 0,584 and the significance was 0,000. The correlation value of smoking with the incidence of andropause was 0,199 and the significance was 0,106. There was an anxiety correlation with the incidence of andropause. There was no correlation of smoking with the incidence of andropause.